(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The present world has been caught in the trap of poverty, unemployment, underemployment and economic disparities etc. In this toughcircumstance Self Help Group programme is appearing as a ray of hope to fight these development enemies. Self Help Groupprogramme is a group based approach which aim to provide financial access at the door step of rural poor, unemployed and weakersection of society and encourage them to start micro enterprise or income generating activities so that they can break the vicious circleof poverty, unemployment and live a dignify life which is the right of every human being. Self Help Group programme is a multidimensionaldevelopment strategy which not only provides easy financial access to poor and weaker section but also work on enhancethem the entrepreneurship, self-confidence knowledge and awareness etc. factors. These factors are played significant role to createemployment opportunities and over all socio- economic development of a society. The Tamil Nadu Corporation for Development ofwomen (TNCDW) was established in 1983 with the prime objective of bringing about socio-economic development and empowermentof women. The Corporation implements Mahalir Thittam, IFAD assisted Post Tsunami Sustainable Livelihoods Programme and alsoSGSY, a major anti-poverty programme meant for self employment of rural poor. Self-help groups (SHGs) in empowering rural womenand their contribution to financial inclusion in India. Economic development can be achieved when resources are equally available andaccessible for all. A Self Help Group is a small economically homogeneous affinity group of the rural poor voluntarily coming togetherto save a small amount regularly, which is deposited in a common fund to meet members emergency needs and to provide collateralfree loans decided by the group. Self Help Group s enhance the equality of status of women as participants, decision-makers andbeneficiaries in the democratic, economic, social and cultural spheres of life